Temporality and gendered agency: Menopausal subjectivities in women's work. (January 2019) - Jack, Gavin; Riach, Kathleen; Bariola, Emily
This article advances feminist organizational theorizing about embodiment and subjectivity by investigating menopause at work as a temporally constituted phenomenon. We ask how time matters in women's embodied and subjective experiences of menopause at work. Theoretically, we draw on feminist writers McNay and Grosz to explore the relationship between gendered agency and time in a corpus of 48 qualitative interviews conducted with women employed at two Australian universities about their experiences of menopause. Our empirical analysis identifies three temporal modalities – episodic, helical and relational – that show how gendered organizational subjectivities are not simply temporally situated, but created in and through distinct temporal forces. We offer two contributions to feminist organizational theory: first, by illuminating the ontological role played by time in gendered agency; and second, by fleshing out the notion of a 'body politics of surprise' with implications for feminist studies of organizational embodiment, politics and ethics.